Diversity, performance and selection of tropical sweet corn inbred lines, and their combining abilities in hybrid combinations - Mustafa, Neyaz Rashid (2019)
Local composite varieties of sweet corn offer moderate yields and eating quality, while imported hybrid varieties are less adaptable to the local environment, although having high eating quality. Therefore, the objectives of this study were (1) to evaluate the potential of 27 tropical sweet corn inbred lines developed from different source populations; (2) to determine genetic diversity among those inbred lines based on agronomic performance and simple sequence repeat (SSR) DNA markers; (3) to identify major heterotic groups among the inbred lines for selection of potential parents for hybrid production; and (4) to evaluate combining abilities among selected parental inbred lines in a half-diallel cross. Performance and heterosis of the single-cross hybrids were evaluated at two different locations, Field 2 and Field 10, Universiti Putra Malaysia, Serdang, Selangor. The genetic distances among the inbred lines as revealed by the SSR DNA markers, were used to predict hybrid performance. A total of 27 near-homozygous sweet corn inbred lines were used in this study, comprising of 25 inbred lines which were developed through continuous selfing and selection from eight source populations, two previously developed inbred lines, and a commercial hybrid variety (Hybrid 530) used as a control, were evaluated for performance. Significant variations in agronomic performance were recorded among the sweet corn inbred lines. Among the inbred lines, the highest husked fresh ear yields were obtained from FTT-1, NTS-2, HSE-2, TNT-1, HAW-4, FTT-3, TNT-2, HAV-3, HAW- 5 and HAV-2, with mean values of 15,875, 15,406, 15,237, 14,722, 14,105, 13,607, 13,556, 13,543, 13,284 and 13,248 kg ha-1, respectively. High genetic diversity was found among the inbred lines evaluated, indicating their good potential for utilization towards production of single cross hybrids. Genetic diversity among the sweet corn inbred lines was also investigated using 100 SSR DNA markers. Among the SSR DNA markers amplified, 77 were found to be polymorphic. Results showed that the SSR markers were informative in detecting genetic differences among the sweet corn inbred lines, as exhibited by high Shannon’s information index (I), Nei’s expected heterozygosity (Nei’s), and polymorphic information content (PIC), with mean values of 0.915, 0.546 and 0.474 respectively. Among the SSR markers amplified, bnlg1447, bnlg1152, umc1867, bnlg1839, umc1858, umc1805 (Appendix 1), umc1030, bnlg1036 and bnlg1176 were found to be the most informative to exhibit genetic diversity in the inbred lines, with PIC values of 0.732, 0.696, 0.682, 0.662, 0.653, 0.638, 0.629, 0.618 and 0.612, respectively. Shannon’s information index , Nei’s gene diversity coefficient and PIC showed that Chromosome 8 was the most informative chromosome (I = 1.060, Nei’s = 0.619 and PIC = 0.544). The inbred lines were further separated into five diverse heterotic groups, based on phenotypic evaluations and six distinct groups based on molecular data. However, since phenotypic and molecular data of the inbred lines were independent of each other, six inbred lines, FTT-1, HAW-1, NTS-2, HSE-4, HAV-2 and EE0-2, were selected as parents based on the molecular data, each from different heterotic groups, to be utilized in a half-diallel cross scheme for the production of single-cross hybrids. Among the hybrids evaluated, hybrids H11, H12 and H15 were found to have the highest husked fresh ear yields in Field 2 (22364, 21252 and 21906 kg ha-1, respectively), Field 10 (21356, 20393, 22623 kg ha-1, respectively), and the locations combined (21860, 20823 and 22265 kg ha-1, respectively). Hybrids that produced high yields were those formed between high × high, high × low or low × low yielding inbred crosses and from genetically diversed population sources. In addition, hybrids H11, H12 and H15 had high and consistent mid- and better-parent heterosis estimates for yield and most yield related traits, indicating that they have accumulated favorable genes acquired by their parental inbred lines. Results of combining ability analysis showed significant additive and non-additive gene actions involved in the control of the traits measured. However, additive gene effects were found to be more important in the control of yield and yield components among the hybrids. Among the parental inbred lines, FTT-1, EE0-2 and HAW-1 had the highest positive and significant GCA effects for husked fresh ear yield in Field 2 (1,415.89, 1,132.22 and 777.89, respectively), Field 10 (975.22, 1,321.89 and 1,204.89, respectively), and the two locations combined (1,195.56, 1,227.06 and 991.39, respectively). This is an indication that these parental lines were the best general combiners among the parental inbred lines for high yield and yield components in the crosses involving them. Among the hybrids produced, P1 × P4 (H3), P4 × P6 (H13), P2 × P4 (H7) and P5 × P6 (H15) were identified as the best combinations, with favorable positive SCA estimates for most of the traits measured. The ratios of GCA to SCA variance (GCA/SCA) were found to be more than 1 for most of the traits measured. This has revealed that both additive and non-additive gene actions were important in the control of these traits although additive gene action was more pronounced. The high broad-sense heritability estimates for most of the traits measured at both and combined locations, is due to a relatively small influence of the environment to the phenotypes. High narrow-sense heritability estimates obtained for most of the traits measured at both locations, indicate the predominance of additive gene actions in the inheritance of all these traits. Results also showed that there was no association between genetic similarities among the six parental sweet corn inbred lines, as revealed by all the SSR DNA markers amplified, and hybrid performances, indicating that the genetic similarities based on SSR markers revealed in the present study were not indicative in predicting hybrid performances. In conclusion, the three best performing hybrids, H11, H12 and H15 were each produced from a combination of two of the three superior inbred lines, FTT-1, EE0-2 and HAW- 1. These inbred lines have proven to consistently show positive and significant GCA effects for yield and most yield related traits. Thus, these potential hybrids should be further tested in large scale multi-locational trials, before they could be released as new tropical sweet corn hybrid cultivars.